2004
DOI: 10.3748/wjg.v10.i18.2711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24 h ultra-marathon on biochemical and hematological parameters

Abstract: Ultra-marathon running is associated with a wide range of significant changes in hematological parameters, several of which are injury related. To provide appropriate health care and intervention, the man who receives athletes on high frequent training program high intensity training programs must monitor their liver and gallbladder function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
143
4
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 32 publications
30
143
4
10
Order By: Relevance
“…Wardyna et al (19) reported a significant increase in the concentration of HTC, HGB, and PLT percentages. In the non-exercising group (young male and female non-athletes), along with an exhaustive aerobic exercise, there was no significant change in the number of WBC, while all other studies reported significant increases in the number of PLT (20)(21)(22)(23). The platelet cycle was heterogeneous in size, density, and reflectivity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Wardyna et al (19) reported a significant increase in the concentration of HTC, HGB, and PLT percentages. In the non-exercising group (young male and female non-athletes), along with an exhaustive aerobic exercise, there was no significant change in the number of WBC, while all other studies reported significant increases in the number of PLT (20)(21)(22)(23). The platelet cycle was heterogeneous in size, density, and reflectivity.…”
Section: Discussionmentioning
confidence: 87%
“…This mechanism can justify the reasons of the affluent increase of platelets in sports. In addition, in extreme steps of platelet activation, such kinds of increases can be caused by formation changes in megakaryocyte components of the cytoplasm (21)(22)(23). There is no consensus on the effects of exercises on platelet concentration and symptoms of platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of variables remain within normal limits despite severe physical stress [80]. These changes are transient and full recovery generally occurs within days and without any apparent long-term adverse consequences [73,76]. For example, a 48-h ultra-marathon caused hypocapnic alkalosis with slight hyperkalemia and hypocalcemia, but no hyponatremia.…”
Section: Pathophysiological Effects Of Ultra-marathon Runningmentioning
confidence: 99%
“…A single bout of strenuous running exercise results in perturbations to numerous biomarkers and the magnitude of changes to biomarkers are proportional to the severity of the running bout [73]. Ultramarathon running can produce changes to biomarkers that are normally associated with pathology of the muscles, liver and heart [74][75][76]. However, also markers of the inflammatory response such as C-reactive protein [77][78][79] and IL-6 [77,79,80] become elevated.…”
Section: Pathophysiological Effects Of Ultra-marathon Runningmentioning
confidence: 99%
See 1 more Smart Citation